KEBIJAKAN PEMUNGUTAN PAJAK RESTORAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) PADA DINAS PENDAPATAN KOTA MANADO - Pusut, Regina Cindi; Tulusan, Femmy (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACTThis watchfulness is done to detect the increase region original income and detect tax acceptance restaurant tax influence towards region original income.This watchfulness aim : (1) how to detect restaurant tax harvest policy execution procedure in increase region original income (2) detect increase region original income in Manado city.Method that used qualitative and data that used restaurant list in Manado city and procedure with regency region original income realization data Manado period 2010 up to year 2015. Data collecting technique that field research (field watchfulness) by interview and observation.Research from this watchfulness has showed that restaurant tax harvest execution procedure as according to this matter by law can influential towards restaurant tax acceptance contribution in regency region original income in Manado city. From year 2010 up to year 2015 experience increase and depreciation. This is caused by restaurant closing existence and development restaurant. This activity is enough influential restaurant tax acceptance, apart from taxpayer obedience is itself.Keyword : restaurant tax, region original income